THE EFFECT OF THE CORONA.JAKARTA.GO.ID SITE OF CONSUMING THIS MEDIUM TO FULFILL THE INFORMATION NEEDS - Muhammad Rizky Arbiyanto; Siti Meisyaroh (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2021)
The existence of the site is still used by many people. The site is a source that can be justified. In accessing a site, there must be a motive for its use. The motives that exist in a person in using a media, where in this research are sites, namely diversion, personal relationships, personal identity, and supervision. The theory that is the basis of this research is the theory of Uses and Gratification. While the data analysis method used in the research is quantitative with the survey method. The test results have shown that the questionnaire that has been given to all respondents is valid and reliable, based on the t test that has been carried out, it can be denied that the fulfillment of information needs by motives and consumption. The influence generated by motive and consumption can be neglected as having a positive effect, this can be seen from the Simple Regression Analysis. Keywords: website, fulfillment of needs, corona virus, COVID-19, motive